Adolescent Depression and Adult Labor Market Outcomes. (1st July 2013) - Fletcher, Jason
Abstract : This article uses recently released data from a national longitudinal sample to present new evidence of the longer term effects of adolescent depression on labor market outcomes. Results suggest reductions in labor force attachment of approximately 5% and earnings reductions of approximately 15% for individuals with depressive symptoms as an adolescent. These effects are only partially reduced when controlling for channels operating through educational attainment, adult depressive symptoms, or co‐occurring illnesses. Further, the unique structure of the data allows for high‐school fixed effects as well as suggestive evidence using sibling comparisons, which allows controls for potentially important unobserved heterogeneity. Overall, the results suggest that the links between adolescent depression and labor market outcomes are quite robust and important in magnitude, suggesting the need for further investments in treatment options and opportunities during adolescence, which will likely result in long term returns.